“At Light Speed”: Attribution and Response to Cybercrime/Terrorism/Warfare. - Brenner, Susan W. (Journal of Criminal Law & Criminology)
This Article explains why and how computer technology complicates the related processes of identifying internal (crime and terrorism) and external (war) threats to social order of responding to those threats. First, it divides the process—attribution—into two categories: what-attribution (what kind of attack is this?) and who-attribution (who is responsible for this attack?). Then, it analyzes, in detail, how and why our adversaries' use of computer technology blurs the distinctions between what is now cybercrime, cyber terrorism, and eyberwarfare. The Article goes on to analyze how and why computer technology and the blurring of these distinctions erode our ability to mount an effective response to threats of either type. Finally, it explores ways in which we can modify how we currently divide responsibility for identifying and responding to the three threat categories among law enforcement and the military, respectively. The goal here is to identify techniques we can use to improve attribution and response processes for emerging cyber threats. Reprinted by permission of the publisher.